An Innovative Learning Assessment Instrument Development Training To Support Merdeka Curriculum Implementation For Teachers At MAN 2 Padang Panjang - Anggriyani, Ria (Pelita Eksakta, 2025)
One important aspect in learning is assessment. Assessment design is not only useful for measuring the achievement of learning objectives, but the results of the assessment can be used as feedback to improve the learning process. The quality of assessment and learning are a complete unity. Good learning quality can be seen from the quality of the assessment, and vice versa, so it is very important for teachers to understand and be skilled in creating appropriate and innovative learning assessment instruments according to curriculum demands. Field data shows that there are still many teachers in Indonesia who are constrained in creating innovative assessment instruments that are in accordance with the Merdeka curriculum. This also happened at MAN 2 Padang Panjang. Efforts made to overcome this problem are by providing training in creating innovative assessment instruments for teachers. The methods used are lectures, demonstrations, questions and answers and guided practice. The results of the evaluation of this activity show that there is an increase in the understanding and skills of teachers in creating innovative learning assessment instruments.